Invasión del matorral por Genista hystrix en una dehesa salmantina (España) - Caro Domínguez, Francisco; Sánchez Anta, María Ángeles; Tarazona Lafarga, Teresa (Ecología Aplicada, 2004)
The invasion of Genisto hystricis-Cytisetum multiflori shrubs in a Salamancan "dehesa" (Quercus forest with low density), was studied using permanent quadrat and transect methodology. The results indicate that, of all shrub species, Genista hystrix Lge. is the predominant invading species in this sclerophyllous formation, due to its growth rate and phenomorphology. The overall invasion rate of this shrub in the "dehesa" has been calculated to be approximately 2.26 m 2 per year
Keywords: "dehesa"; Cytisus multiflorus (L'Hèr.) Sweet.; Cytisus scoparius (L.) Link; dynamics; Genista hystrix Lge.; Invasive species; Quercus rotundifolia Lam.; Salamanca; sclerophyllous; Shrubs

Invasión del matorral por Genista hystrix en una dehesa salmantina (España) - Caro Domínguez, Francisco; Sánchez Anta, María Ángeles; Tarazona Lafarga, Teresa (Ecología Aplicada, 2004)
The invasion of Genisto hystricis-Cytisetum multiflori shrubs in a Salamancan "dehesa" (Quercus forest with low density), was studied using permanent quadrat and transect methodology. The results indicate that, of all shrub species, Genista hystrix Lge. is the predominant invading species in this sclerophyllous formation, due to its growth rate and phenomorphology. The overall invasion rate of this shrub in the "dehesa" has been calculated to be approximately 2.26 m 2 per year
Keywords: "dehesa"; Cytisus multiflorus (L'Hèr.) Sweet.; Cytisus scoparius (L.) Link; dynamics; Genista hystrix Lge.; Invasive species; Quercus rotundifolia Lam.; Salamanca; sclerophyllous; Shrubs

Two vegetation maps of the same island: floristic units versus structural units - Lux, Andrea; Bemmerlein-Lux, Florian A (Applied Vegetation Science, 1998)
Abstract. This paper presents a comparison of two alternative methods to describe and map vegetation: on the basis of plant species and growth forms, respectively. A stratified random sampling was taken from spontaneous vegetation in 1989 on the volcanic island of Pantelleria (near Sicily, Italy). Cartographic and other comparisons of the results from classification and ordination analysis suggest that the major differences were associated with differences in the time scale of the underlying processes. Species results (leading to floristic vegetation units) were representative of longer-term processes, growth-form results (leading to structural vegetation units) with shorter-term processes. Further implications of these results are discussed.
Keywords: dynamics; fire; growth form; Italy; Pantelleria; structure; succession; Temporal scale

Germination of Quercus ilex and Q. pubescens in a Q. ilex coppice - Bran, D; Lobreaux, O; Maistre, M; Perret, P; Romane, F (Plant Ecology, 1990)
Quercus ilex L. (holm oak) coppices, widespread around the Mediterranean basin, are probably the result of 5 000 years of prolonged human disturbance of the original Quercus pubescens Willd. (downy oak) forests. Since disturbance has almost ceased in recent years, a question arises as to the development of these coppices: will the Q. pubescens forests return, or will Q. ilex remain the dominant species? To investigate the phenomenon, we analyzed the first stages, i.e. germination of the two species in holm oak coppices. Our experiments show that both species germinated better in coppices than in clearings or clear-cuts. Moreover, Q. pubescens appears to be slightly favored above Q. ilex and it is suggested auto-allelopathy is involved, at least partially inhibiting the germination of Q. ilex.
Keywords: dynamics; Mediterranean climate; Southern France; succession